The youth involvement towards political issues in social media / Fatiha Suliman and Mohd. Nizamuddin Noding - Suliman, Fatiha; Noding, Mohd. Nizamuddin (2015)
Social media plays a vital role in this digital era. It helps people in terms of communication and sharing of information by ignoring the geographical distances and time. Youth are the common group that using social media at the most of time by updating their status, sharing information and for entertainment. Besides, political issues also have the part to play in the social media as well. This paper examines the involvement of youth towards political issues through social media, and what will influence the involvement of the youth as keyboard warrior in political issue.